Not enough can be enough: feasibility of the Idylla EGFR mutation test when reuse of stained tissue slides is the only option available. Issue 12 (16th August 2021) - Ercolani, Cristiana; Di Benedetto, Anna; Bonomo, Claudia; Visca, Paolo; Palange, Aldo; Assisi, Daniela; Forcella, Daniele; Terrenato, Irene; Pescarmona, Edoardo; Ciliberto, Gennaro; Cecere, Fabiana Letizia; Cappuzzo, Federico; et al.
Abstract : Aims: The minimally invasive procedures used in the diagnostic workup of patients with advanced non-small cell lung cancer (NSCLC) often provide poor yields of pathological material suitable for molecular analyses. Not infrequently, the DNA yield from small biopsies/cytological samples is insufficient for the assessment of genomic biomarkers that inform personalised therapies. The Idylla EGFR mutation test (IEMT) has been specifically designed to process formalin-fixed paraffin-embedded sections without requiring preliminary DNA extraction. This study aims to evaluate the diagnostic accuracy of IEMT when used to analyse archival histopathology material. More specifically, our objective was to establish whether or not different staining procedures could affect assay performance. Methods: Twenty NSCLC samples were selected accordingly to EGFR mutational status. To mimic archived stained material, sections were subjected to H&E staining, fluorescent in situ hybridisation analyses or immunodetection by immunohistochemistry before being processed for IEMT. Results: Parallel assessment of EGFR mutational status by IEMT on stained sections and next-generation sequencing on DNA yielded a concordant result in 50 out of 60 tests (83.3%). The discoloration of H&E of the archived sample was found to be the optimal procedure to highlight all the actionable alterations of EGFR . Conclusions: IEMT can provide remarkable diagnostic accuracy for the assessment of EGFR mutational status also when the only source of pathological material available for molecular analyses is represented by H&E stained sections. Ad hoc supervision by a qualified molecular biologist is in any case recommended.